Ethnofuturism and Traditional Udmurt Ideas about the Future - Bogdan V. Anfinogenov (Финно-угорский мир)
Introduction. The problem of the traditional ideas of the Udmurt people about time and space, including their attitude to the future, is significant for modern science. Despite the numerous publications on this issue, there is practically no research on the refraction of traditional Udmurt ideas about the future in the Udmurt ethnofuturist movement, and their vision of the future of ethnic culture in this context. The purpose of the study is to try to fill this gap by examining and analyzing exactly what traditional ideas exist in Udmurt culture and how ethnofuturists use them in their work.